A penetrating metal-organic framework based on N-heterocyclic carboxylic acid with sensing properties toward Cr(VI)/Fe(III) and nitrobenzene. Issue 16 (17th September 2018) - Zong, Ziao; Fan, Yuhua; Xu, Cungang; Zuo, Shanshan; Yan, Fei; Meng, Xiangmin; Zhang, Xia; Bi, Caifeng
Abstract: A luminescent metal-organic framework, [Cd(tmlb)(bbibp)] n (1 ) (H2 tmlb = (1 H -1, 2, 4-triazol-1-yl)methylenebis(benzonic acid), bbibp = bis(benzoimidazo-1-ly)biphenyl), has been solvothermally synthesized and characterized by elemental analysis, infra-red spectroscopy, single-crystal X-ray diffraction, thermogravimetric analysis, and powder X-ray diffraction. Complex1 exhibits two interpenetrating uninodal 4-connected 3-D frameworks with a (6 5 ·8) topology. The luminescence studies reveal that the complex displays sensitive and selective luminescence sensing toward Cr(VI) (CrO4 2− and Cr2 O7 2− ) anions, Fe(III) cation, and nitrobenzene. The potential quench mechanism was discussed. Graphical Abstract: